(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aims to investigate the nature of the correlated relationship between emotional regulation and resilience, as well as to investigate the differences according to the gender. Emotional Regulation Scale for Adolescents (prepared by Al-Assemi) and Resilience Scale (prepared by Connor and Davidson) have been used. The sample was (40) students of 2nd year of secondary school in Sweidaa Governorate. The concluded results are: There is a statistically significant relationship between emotional awareness and resourcefulness or intelligence; as well as there is a statistically significant relationship between emotion self-regulation and both resourcefulness and the total mark of resilience. Moreover, there is a statistically significant relationship between cognitive regulation and the total mark of resilience, as well as there is a statistically significant relationship between the social context and both hardiness and the total mark of resilience. Furthermore, there is a statistically significant relationship between the total mark of emotional regulation and both hardiness, resourcefulness, and the total mark of resilience. There are no statistically significant score differences in resilience between high and low emotional regulation levels among the sample members. There are statistically significant score differences in emotional regulation on emotionl awareness, social context, and total mark of emotional regulation related to gender, in favor or male members. Moreover, there are no statistically significant differences in emotional cognition, emotional self-regulation, expression suppression, and emotional infection dimensions.‎ There are no statistically significant score differences in resilience related to gender.‎ And There is statistically significant effect between resilience and gender variables together in emotional regulation, in favor of high-scored resilence male members; as well as there is no statistically significant effect of resilience alone or gender alone in emotional regulation.